Traumatic Memory of One's Son Gone Missing in War: Content Analysis Using Krippendorff's Alpha. (March 2019) - Kozina, Slavica; Kowalski, Martin; Vlastelica, Mirela; Mastelić, Tonći; Borovac, Josip A.
Our aim was to determine (a) how parents deal with experiences like having a son missing in war, and (b) what expectations they have in terms of outcomes. This qualitative study included 29 parents of 21 sons gone missing in war. We used content analysis singling out narrative patterns and coded these. We assessed intercoder reliability using Krippendorff's alpha coefficient. Items passing the Krippendorff's alpha threshold of ≥.50 were verified using Cronbach's alpha. Three of five coders showed acceptable intercoder agreement on 23 of the 173 identified topics (13.3%; Krippendorff's alpha: .50-.82). Cronbach's alpha coefficient confirmed intercoder reliability of .7903. Fathers' narratives differ from mothers'. Statistics are a valuable tool for identifying specific motifs in grieving narratives of parents who have lost their child. Content analysis can provide insights without interfering with authentic personal experience sparing interviewees from reliving the traumatizing experience.